(untitled) (Journal of actual problems of jurisprudence, 2018)
The article is devoted to the study of the problems of recognizing a commission’s contract as invalid, namely from the point of view of establishing specific conditions for declaring it invalid and also, the legal regulation of the relations of the parties after the recognition of mentioned contract as invalid. The relevance of the research topic is determined by several factors based on the need to study issues of scientific-theoretical, legislative nature. As a special type of contract, the contract of commission, along with domestic legislation, is governed by the laws of Germany, France, and Switzerland. In countries with a dualistic private law system, a commission agreement is treated as a trade transaction and is governed by trade codes. The most complete contract and related relations are settled in GSU and SHOZ. In the modern capitalist turnover, a commission agreement is mediated by various kinds of banking operations, the subject of which is primarily securities. In the regulation of such operations a special place is occupied by standard contracts developed by banks. This contractual form is also used for the purchase and sale of goods, chartering and other transactions, not only in domestic but also in foreign trade as a means of penetrating markets. The importance of this study is growing due to the fact that this type of contract is common not only in the Kazakhstan market, but also around the world, and because of the standard form of a contract, in practice, problems often arise with the termination and invalidation. In addition, in domestic science there is no comprehensive theoretical study of this topic from a legal point of view. This work aims to determine the conditions, the consequences of the recognition of the contract commission void. In the course of the study, general scientific, historical and comparative analysis methods were used. The legal analysis carried out by the authors makes it possible to provide recommendations on how to improve the national legal regulation of these problems. Key words: committent, contract of commission, restitution, consequences of a transaction being declared invalid.